10: FACULTY DEVELOPMENT SCHOLARSHIP: AN ANALYSIS OF TO IMPROVE THE ACADEMY, 1982–2011. (10th October 2017) - Linder, Kathryn E.
Abstract : As To Improve the Academy enters its thirty‐second year, this chapter offers a retrospective to honor the history of the field through a timely analysis of the content published in TIA and editorial and authorship trends over the previous three decades. Frequency distributions identify the most published authors, their institutional affiliations, the most written about topics, and patterns of collaborative authorship in volumes 1 (1982) through 30 (2011), and findings from a citation analysis of ten years of TIA (volumes 21–30), highlight trends in resources cited and types of resources .